The effects of machine parameters on the integrity of WC-Ni coatings deposited onto titanium parts with laser additive manufacturing - Van Coller, Marius Cornelius (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.